Oil Exports, Political Issues, and Stock Market Nexus - Asaad, Zeravan Abdulmuhsen; Al-Delawi, Amjad Saber; Fatah, Omed Rafiq; Saleem, Awaz Mohamed (International Journal of Energy Economics and Policy, 2023)
This study investigates the influence of oil export and political issues on Iraq’s stock exchange using various Ordinary Least Square regression models. The empirical results show that the model’s effect is not similar based on the explanatory variables included, such as the Covid-19 outbreak, financial crisis, parliament elections, and ISIS emergence are not significant. In contrast, the internal conflict, oil export, and oil prices are substantial effects on the index of the Iraq stock exchange from (2004 to 2021); researchers in the literature have neglected this market due to its novel establishment after (2003). Moreover, the market capitalization still considers very small compared to the regional financial markets. The study contributes to the existing knowledge because most studies on stock market determinants consider political, economic, democratic, or governmental factors. In contrast, here, most elements included using new measurements, such as the internal conflict by cutting off the financial share of the Kurdistan region from the central state budget. Finally, the analysis incorporates the conclusions with straightforward suggestions that policymakers can use, government, investors, and supervisors to control the stock market risk.